Ferromagnetic resonance in double perovskite epitaxial thin films of La2NiMnO6 on SrTiO3 and NdGaO3 substrates - (:unkn) unknown (AMER INST PHYSICS, 2010)
Ferromagnetic resonance (FMR) studies of epitaxial La2NiMnO6 (LNMO) thin films on (100) oriented SrTiO3 and (110) oriented NdGaO3 substrates at room temperature are presented. Observation of FMR spectra above the Curie temperature of this compound confirms the presence of magnetic ordering in LNMO thin films at room temperature. Best fitting of FMR spectra has been made on the assumption of the coexistence of two magnetic phases with different easy and hard axis periodicities in the film plane of LNMO. The spectra of the films on various substrates are characterized by different in-plane and out-of-plane symmetries, which indicates the existence of different epitaxial growth on the substrates with different crystal symmetries and orientations. (C) 2010 American Institute of Physics. [doi:10.1063/1.3481678]
Keywords: crystal orientation; crystal symmetry; Curie temperature; epitaxial layers; ferromagnetic resonance; lanthanum compounds; neodymium compounds; nickel compounds; strontium compounds